Predictors of post‐thrombotic syndrome in a population with a first deep vein thrombosis and no primary venous insufficiency. Issue 3 (13th March 2013) - Galanaud, J. P.; Holcroft, C. A.; Rodger, M. A.; Kovacs, M. J.; Betancourt, M. T.; Wells, P. S.; Anderson, D. R.; Chagnon, I.; Le, G.; Solymoss, S.; Crowther, M. A.; Perrier, A.; et al.
Summary Background Post‐thrombotic syndrome (PTS) is the most frequent complication of deep vein thrombosis (DVT). Its diagnosis is based on clinical characteristics. However, symptoms and signs of PTS are non‐specific, and could result from concomitant primary venous insufficiency (PVI) rather than DVT. This could bias evaluation of PTS. Methods Using data from the REVERSE multicenter study, we assessed risk factors for PTS in patients with a first unprovoked unilateral proximal DVT 5–7 months earlier who were free of clinically significant PVI (defined as absence of moderate or severe venous ectasia in the contralateral leg). Results Among the 328 patients considered, the prevalence of PTS was 27.1%. Obesity (odds ratio [OR] 2.6 [95% confidence interval (CI) 1.5–4.7]), mild contralateral venous ectasia (OR 2.2 [95% CI 1.1–4.3]), poor International Normalized Ratio (INR) control (OR per additional 1% of time with INR < 2 during anticoagulant treatment of 1.018 [95% CI 1.003–1.034]) and the presence of residual venous obstruction on ultrasound (OR 2.1 [95% CI 1.1–3.7]) significantly increased the risk for PTS in multivariable analyses. When we restricted our analysis to patients without any signs, even mild, of contralateral venous insufficiency (n = 244), the prevalence of PTS decreased slightly to 24.6%. Only obesity remained an independent predictor of PTS (OR 2.6 [95% CI 1.3–5.0]). Poor INR control and residual venous obstruction also increased the risk, but the results were no longer statistically significant (OR 1.017 [95% CI 0.999–1.035] and OR 1.7 [95% CI 0.9–3.3], respectively). Conclusions After a first unprovoked proximal DVT, obese patients and patients with even mild PVI constitute a group at increased risk of developing PTS for whom particular attention should be paid with respect to PTS prevention. Careful monitoring of anticoagulant treatment may prevent PTS.